Quality assurance in higher education in the Middle East : practices and perspectives - Saeed, Sameerah T.; Sherwani, Karwan H. (Innovations in higher education teaching and learning, 2023)
As Middle Eastern countries strive to develop and achieve excellence across their higher education systems, meeting and exceeding international standards, such as quality assurance and accreditation, have become vital targets for higher education institutions in the region. Featuring case studies from Egypt, Iraq, Lebanon, Saudi Arabia, and United Arab Emirates, chapters highlight institutional arrangements designed to prioritise quality assurance and the challenges faced in these countries' quality-seeking experience. Offering critical perspectives and recommendations to guide future academic leaders, chapters also provide ways to ensure better practices and assist in the development of the quality assurance process. An essential resource for institutional leaders across the Middle East, as well as those invested in the development of higher education in the region, Quality Assurance in Higher Education in the Middle East acts as a unique contribution for propelling the progress of higher education in the Middle East.